Multi-Scenario Simulation of Ecosystem Service Value in Beijing’s Green Belts Based on PLUS Model - Ziying Hu; Siyuan Wang (Land)
Urbanization and economic growth have substantially modified the land utilization structure, affecting ecosystem services and their spatial distribution. As a crucial component of Beijing’s urban framework, the city’s green belts, located at the periphery of its core metropolitan area, play a vital role in supplying urban ecosystem services. They also represent a focal point for land use transformation conflicts, making them an important study area. This research utilizes land utilization data from 2000, 2005, 2010, 2015, and 2020 as the primary dataset. It adopts a modified standard equivalent factor and integrates it with the Patch-Generaling Land Use Simulation (PLUS) model to model land utilization in Beijing’s green belts for 2035 under three scenarios: the natural development scenario (NDS), ecological protection scenario (EPS) and cultivated protection scenario (CPS). The study aims to analyze and project the spatial and temporal evolution of ecosystem service values (ESVs) in 2035 under different scenarios in the green belts of Beijing. The results indicate that (1) land use in Beijing’s green belts is dominated by cropland and construction land. Construction land has expanded significantly since 2000, increasing by 500.78 km2, while cropland has decreased by 488.47 km2. Woodland, grassland, and water have also seen a reduction. Overall, there is a trend of woodland and water being converted into cropland, with cropland subsequently transitioning into construction land. (2) In the NDS, construction land increases by 91.76 km2, while cropland, grassland, and water decrease. In EDS, the growth of construction land decelerates to 22.09 km2, the reduction in cropland decelerates, and the conversion of cropland to construction land is limited. Grassland and water remain largely unchanged, and woodland experiences a slight increase. In CPS, the conversion of cropland to construction land is notably reduced, with construction land increasing by 11.97 km2, woodland increasing slightly, and grassland and water decreasing slightly. (3) The ESV ranking across scenarios is as follows: EPS 1830.72 mln yuan > CPS 1816.23 mln yuan > NDS 1723.28 mln yuan. Hydrological regulation and climate regulation are the dominant services in all scenarios. ESV in EPS attains the greatest economic gains. This study contributes to understanding the effects of land utilization changes on ESV, offering valuable empirical evidence for sustainable development decision-making in swiftly urbanizing areas.